Sustaining sulfate ions throughout smart water flooding by nanoparticle based scale inhibitors - Safari, Mehdi; Rahimi, Ali; Lah, Rainnie Mering; Gholami, Raoof; Khur, Wee Siaw (ELSEVIER, 2020)
Smart water flooding (SWF) has been successfully implanted in many fields around the world for the past decades. In this approach, smart water is injected into the reservoir to change the surface characteristics of rocks and improve the oil recovery. However, the presence of sulfate ions in the smart water and their interactions with the cations dissolved in the formation water (FW) may generate what is called scale. There have been several approaches proposed so far to inhibit the scale formations under different conditions but limited success has been reported to the application of these methods once tested under the reservoir conditions. In this paper, a nanomaterial based approach is proposed to inhibit the scale formation during SWF. Nano Glass Flakes (NGFs) and nano silica were considered as two effective nanomaterials in this study and a series of measurements were made to ensure that the scale formation can be inhibited under different temperature and salinity conditions. The results obtained indicates that if the nanoparticles can be properly dispersed in the smart water solution, the likelihood of the scale formation can be significantly decreased and the conductivity can be increased to 0.69 and 0.65 mS/cm for NGFs and nano silica solutions at 50 °C. It appears that NGFs provide a far better performance as temperature rises while nano silica loses its performance. It is also found that the nanoparticles perform better in a high saline water and can be an effective choice for SWF in the concentration of 0.05 wt%. It is also noted that the conductivity improvement made by NGFs in a high salinity water is 0.9 mS/cm while that for water with a low salinity conductivity is 0.23 mS/cm. Given the fact that the nanoparticles used has huge negative surface charge, reduction of the scale formation might be linked to the cations adsorption in the solution but may need further studies.